Teachers’ Assessment Problems for Children with Special Needs in Elemantary Schools - Een Ratnengsih (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2018)
The teachers’ problems arise because there is still a lack of teacher skills in assessing learning needs for children with special needs, as a result the learning design and implementation is not optimal. This study aims to describe teachers’ constraints in implementing assessment skills for children with special needs using qualitative descriptive research method. The study involved 32 teachers representing 32 inclusive schools in West Java. The data were collected through an open-ended questionnaire and analysed using coding techniques. The results show some obstacles faced by teachers in assessing the needs of children with special needs such as the low level of teachers’ understanding in developing the instrument, unclear guidlinesfor the assessment, and the media and time to assess. Therefore, the assessment process is hampered and has an impact on the low quality of learning for the children in inclusive schools.